Dysfunction of lipid storage droplet-2 suppresses endoreplication and induces JNK pathway-mediated apoptotic cell death in Drosophila salivary glands. - Binh, T.D.; Nguyen, Y.D.H.; Pham, T.L.A.; Komori, K.; Nguyen, T.Q.C.; Taninaka, M.; Kamei, K. (Scientific reports, 2022)
The lipid storage droplet-2 (LSD-2) protein of Drosophila is a homolog of mammalian perilipin 2, which is essential for promoting lipid accumulation and lipid droplet formation. The function of LSD-2 as a regulator of lipolysis has also been demonstrated. However, other LSD-2 functions remain unclear. To investigate the role of LSD-2, we performed tissue-specific depletion in the salivary glands of Drosophila using a combination of the Gal4-upstream activating sequence system and RNA interference. LSD-2 depletion inhibited the entry of salivary gland cells into the endoreplication cycle and delayed this process by enhancing CycE expression, disrupting the development of this organ. The deficiency of LSD-2 expression enhanced reactive oxygen species production in the salivary gland and promoted JNK-dependent apoptosis by suppressing dMyc expression. This phenomenon did not result from lipolysis. Therefore, LSD-2 is vital for endoreplication cell cycle and cell death programs.